Bach, Mozart, and Beethoven: Sorting piano excerpts based on perceived similarity using DiSTATIS. (April 2020) - Raman, Rachna; Kriegsman, Michael A.; Abdi, Hervé; Tillmann, Barbara; Dowling, W. Jay
Abstract: Our initial aim in this study was to show that Western listeners can sort the music of 3 Western composers consistently on the basis of their compositional style. We found that they could, and proceeded to investigate what cues they might be using to accomplish that task, as well as whether their use of those cues was related to their level of musical training. In Experiment 1, we presented 21 excerpts from the keyboard music of Bach, Mozart, and Beethoven, each excerpt linked to an icon on the computer screen. Participants were to place the icons in different groups following the rule that the icons in one group could have been written by the same composer. First, they did a free sort in which they could form as many groups as they liked, and then we told them that there were just 3 composers, and they should make 3 groups in a constrained sort. In Experiment 1, the excerpts were produced with MIDI transcriptions of the scores, such that the composer's pitch and time information of the notes was preserved, but there was no variation in tempo, dynamics (loudness), or articulation (connectedness or separateness of notes in time). In spite of this simplification, listeners succeeded in clearly differentiating the composers in the constrained sort. In Experiment 2, we used more natural stimuli, 36 excerpts taken from recordings of the 3 composers by 4 pianists who had recorded substantial amounts of each: Arrau, Barenboim, Pirès, and Richter. Here, the stimuli included all the expressive cues of a live performance, and in the constrained sort listeners were even better at categorizing the composers, with not very much difference between the categorizations of trained and untrained listeners. Their judgments were also strongly influenced by the pianists. Richter's performances of the 3 composers were clustered relatively close to the Mozart region of the solution, indicating their clarity and balance; in contrast, those of Barenboim were clustered in the Beethoven region, indicating their sumptuousness and passion. We used a relatively new approach to data analysis—DiSTATIS—which provided the possibility of projecting the sorting results viewed from various perspectives—composer, pianist, participant expertise—into the same space, giving a clearer picture of the results than a piecemeal account of those perspectives.